PENGARUH BRANDING TERHADAP PERILAKU KONSUMEN - Tri Esti Masita (Majalah Imiah Manajemen & Bisnis, 2020)
Customer-based brand equity (CBBE) is a differential effect which is owned brand knowledge on consumer response to marketing the brand. The principle of customer-based brand equity model is that the strength of the brand lies in what is seen, read, heard, learned, thinking and feeling about the brand customers all the time. The purposes of branding is giving power of the brand on the product or service as opposed to another. This article is the research developed the conceptual framework of the model Mohammad Reza Jalivand at al (2011) that integrates customer-based brand equity and the theory of planned behavior carried out in Purwokerto’s sociaty` Data were collected and analyzed from 113 respondents. The results using analysis tools Structural Equation Modeling AMOS 16.0 indicates that the variable brand equity consists of brand awareness, brand association, perceived quality and loyalty largely influence the behavior of the premeditated consisting of affective attitude, subjective norm, and control the behavior that ultimately affect consumer intentions to behave choose the brand. There are two variables that are not significant in this research,that are the brand awareness of the subjective norm, and perception of quality to control behavior. To overcome this, required complete information and interesting conducted by the salesperson or personal selling that brand closer and embedded in the minds of consumers are expected to motivate target consumers to prefer the brand delivered